METAANALYSIS OF EFFECT USING PREDICT, DISCUSS, EXPLAIN, OBSERVE, DISCUSS, EXPLAIN (PDEODE) LEARNING MODELS ON STUDENT LEARNING OUTCOMES TO FOUR INDICATORS - tetri ramadhani amelya (PILLAR OF PHYSICS EDUCATION, 2022)
The outcome of the research to determine student learning at 3 levels of education using  PDEODE  model. The result  were researched from 8 international journals. Method used in this research are  meta-analysis. Meta-analysis is defined as a technique in statistics to describe the results of two or more studies in order to obtain quantitative data guidance. The conclusion of this study specify to manage the PDEODE model has a good effect on student learning achievement.